2006
DOI: 10.1159/000096038
|View full text |Cite
|
Sign up to set email alerts
|

Time Relation between a Syncopal Event and Documentation of Atrioventricular Block in Patients with Bifascicular Block: Clinical Implications

Abstract: Background: Transient high-degree atrioventricular (AV) block is a common cause of syncope in patients with bifascicular block (BFB) but the intermittent nature of AV block makes ECG documentation a challenge. A sensitive and safe tool to investigate BFB patients with syncope would be a bradycardia-detecting pacemaker, which provides a possibility of studying the time relation between the index syncopal episode and the development of high-degree AV block. Methods: Twenty-seven patients with BFB and syncope wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…[20][21][22][23][24][25][26][27] Although a thorough assessment of AVB development (especially those of transient nature) was not possible in our study, a conservative estimate for the development of a class IA indication for pacemaker, mainly due to AVB, was found in 13% of patients, with the event occurring most likely within a year from their enrollment. Differences in symptomatic AVB occurrence between the 2 groups showed that AVB was mainly recognized in the DDD30 group; this is explained by the fact that in the DDD60 group all blocks of transitory origin were not detected.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26][27] Although a thorough assessment of AVB development (especially those of transient nature) was not possible in our study, a conservative estimate for the development of a class IA indication for pacemaker, mainly due to AVB, was found in 13% of patients, with the event occurring most likely within a year from their enrollment. Differences in symptomatic AVB occurrence between the 2 groups showed that AVB was mainly recognized in the DDD30 group; this is explained by the fact that in the DDD60 group all blocks of transitory origin were not detected.…”
Section: Discussionmentioning
confidence: 80%
“…7,20,23,24 In addition, several studies focusing on follow-up of BFB patients with previous syncope reported consistent rates of temporary or permanent AVB development over time. 8,11,[25][26][27][28] Despite the high incidence of electric disturbances of the conduction system, EPS at the time of the hospital observation has limited positive predictive value. 10,14,29,30 Accordingly, BFB patients with both history of previous syncope and a negative EPS have been the subject of several investigations involving pacemakers or loop recorders to identify the nature of associated syncopal recurrences and consequently its most appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have analysed the clinical involvement of BFB [9][10][11] and its relation to syncope of unknown origin 3,[12][13][14][15][16] . According to the latest pacing clinical practice guidelines, and summarizing available evidence, syncope in patients with BFB and an abnormal EPS should receive a pacemaker.…”
Section: Discussionmentioning
confidence: 99%
“…The composite primary end point occurred in 23 patients, whereas only 14 patients developed a class I indication for permanent pacing during the course of the study. In addition, several studies focusing on the outcome of patients with BFB and previous syncope reported consistent rates of AV block development over time [38]. However, none of these studies was designed to identify clinical predictors of bradyarrhythmic events necessitating PM implantation.…”
Section: Right Bundle Branch Blockmentioning
confidence: 99%